Implementation Social Media Marketing Implementation in MSMEs - I Nyoman Tri Sutaguna; Norvadewi Norvadewi; Betty Rahayu; Arief Yanto Rukmana; Maria Lusiana Yulianti (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
One of the regencies in West Java Province with a sizable number of MSMEs is Sumedang. In the village of Kutamandiri, there is one prospective SMEs. According to the survey results, one MSME actor producer named Basreng Masrifah has never used social media marketing to grow his company. Remembering that social media marketing has a favourable association with future business continuity, MSMEs need to implement it immediately. Students from and the Office of Cooperatives and Micro Small Enterprises of Sumedang Regency worked together to complete this act of community service. By making the Tokopedia marketplace one of the marketplaces that is heavily used by the larger community, this community service project aims to help address problems while also offering aid to MSME players connected to the vicinity of social media marketing. The process of putting this activity into action is broken down into three stages: outreach, training, and mentorship of the MSME in question. The desired outcome of this activity is that MSME actors will be able to comprehend the significance of social media marketing and be able to apply it to their businesses.